2022
DOI: 10.3390/jmse10081061
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Infrasonic Geosphere Waves Caused by Explosive Eruption of Hunga Tonga-Hunga Haʻapai Volcano

Abstract: The paper presents the results of processing recordings of abnormal signals, which originated during the eruption of Hunga Tonga-Hunga Haʻapai volcano, and were registered by a laser nanobarograph and two laser strainmeters; there were three meters of sea-level variations, located in the Sea of Japan, and twelve meters of sea-level variations, located in the Pacific Ocean. Acoustic-gravity Lamb waves, generated in the atmosphere, caused disturbances of similar periods in the Earth’s crust, which were registere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
6
0
2
Order By: Relevance
“…Fluctuations of long periods (from 30 min 07.6 s to 31 min 59.1 s) were previously identified in the records of sea level fluctuations during an atmospheric pulse’s passage over the Sea of Japan, resulting from the explosion of the Hunga Tonga-Hunga_Ha’apai volcano [ 15 ]. The origin of this oscillation was first explained by the excitation of one of the seiches of the Sea of Japan, but later it was found that these oscillations are caused by eigen oscillations of the ionosphere, i.e., Lamb waves.…”
Section: Discussionmentioning
confidence: 99%
“…Fluctuations of long periods (from 30 min 07.6 s to 31 min 59.1 s) were previously identified in the records of sea level fluctuations during an atmospheric pulse’s passage over the Sea of Japan, resulting from the explosion of the Hunga Tonga-Hunga_Ha’apai volcano [ 15 ]. The origin of this oscillation was first explained by the excitation of one of the seiches of the Sea of Japan, but later it was found that these oscillations are caused by eigen oscillations of the ionosphere, i.e., Lamb waves.…”
Section: Discussionmentioning
confidence: 99%
“…Двадцать седьмого марта 1954 г. на атолле Бикини в архипелаге Маршалловы острова Соединенные Штаты провели испытание первой в мире термоядерной бомбы, акустические волны от которого достигли Японии и были зарегистрированы на расстоянии около 3900 км [Yamomoto, 1954]. Акустические сигналы, появившиеся в результате испытания советской термоядерной бомбы на Новой Земле мощностью 57 Мт в октябре 1961 г., имели схожую структуру с сигналами от извержений вулканов [Donn, Ewing, 1962], из-за колоссальной мощности взрыва совершили несколько проходов вокруг земного шара и были зафиксированы на севере Шотландии (Aberdeen) [Госсард, Хук, 1978;Donn, Ewing, 1962;Carpenter et al, 1961]. Акустические сигналы анализировались и сопоставлялись с ранее наблюдаемыми атмосферными волнами от крупного извержения вулкана Кракатау 1883 г., c атмосферным эффектом от падения Тунгусского метеорита 1908 г. Сравнительный анализ естественных сигналов и теоретических барограмм для многослойной среды дал возможность объяснить структуру полученного акустического сигнала [Harkrider, 1964].…”
Section: историческая справкаunclassified
“…8 представлены полученные после увеличения шага дискретизации данных и фильтрации вариации атмосферного давления по записям нанобарографа и смещений земной поверхности по данным деформографов. Описание используемой аппаратуры приведено в статье [Dolgikh et al, 2022b].…”
Section: материалы и методыunclassified